2019
DOI: 10.1111/ijpo.12507
|View full text |Cite
|
Sign up to set email alerts
|

Associations of sleep patterns with metabolic syndrome indices, body composition, and energy intake in children and adolescents

Abstract: Background: Self-reported short sleep duration is associated with greater risk for metabolic syndrome (MetS), obesity, and higher energy intake (EI). However, studies of these associations in children using objective methods are sparse. Objectives: To determine the associations for sleep patterns with MetS indices, body composition, and EI using objective measures in children. Methods: Free-living sleep and physical activity were measured in 125 children (aged 8–17y, BMI-z=0.57±1.0, 55% female) using wrist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 46 publications
6
38
1
7
Order By: Relevance
“…In agreement with our findings, He et al found that high variability in sleep duration, but not mean sleep duration, was associated with greater central adiposity [18]. However, we did not find an association between average bedtime and blood pressure, as demonstrated by Mi, et al in a group of mostly younger adolescents (12.4 ± 2.6 y) [17]. It is also worth noting that our Icelandic cohort was generally lean, with a 12% prevalence of overweight and obesity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with our findings, He et al found that high variability in sleep duration, but not mean sleep duration, was associated with greater central adiposity [18]. However, we did not find an association between average bedtime and blood pressure, as demonstrated by Mi, et al in a group of mostly younger adolescents (12.4 ± 2.6 y) [17]. It is also worth noting that our Icelandic cohort was generally lean, with a 12% prevalence of overweight and obesity.…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to our hypothesis, we did not observe a relationship between mean bedtime or average sleep duration and metabolic risk factors. While a number of previous studies have noted a positive association between self-reported short sleep and obesity in adolescents [32], some more recent studies find a lack of this relationship while measuring sleep with actigraphy [17, 18]. In agreement with our findings, He et al found that high variability in sleep duration, but not mean sleep duration, was associated with greater central adiposity [18].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Laboratory studies in adults have shown that short sleep duration could affect appetite regulation through relevant hormonal change, specifically leptin and ghrelin . This may cause excessive food intake and eventually increase energy intake, which has been found in epidemiological studies in both school‐aged and preschool‐aged children . On the other hand, short total sleep duration may also contribute to increased adiposity by reducing energy expenditure .…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep has been linked to an increased risk of obesity among children and adults [109][110][111][112]. There is also some evidence that short sleep length is associated with unhealthy diet and eating patterns that favor energy dense foods, such as fast food and candy, in children and adolescents [113,114]. A recent study found that shorter sleep duration (<8 h) in adolescents is related to an increased consumption of fats and a decreased intake of carbohydrates that may predispose them to an increased risk of obesity [115].…”
Section: Sleep and The Brainmentioning
confidence: 99%